2020
DOI: 10.7202/1070247ar
|View full text |Cite
|
Sign up to set email alerts
|

Impacts de la légalisation du cannabis récréatif sur la santé mentale : une recension des écrits

Abstract: Méthode Cette recension a été effectuée dans la base de données PubMed en utilisant la combinaison de termes associés au cannabis, à la légalisation et à la santé mentale. Deux évaluateurs indépendants ont ensuite examiné 272 titres et résumés, puis ont conservé 11 articles.Résultats À la suite de la révision des articles, nous constatons que la plupart des études ciblant la consommation de cannabis décrivent une prévalence croissante d'utilisateurs. Il est à noter qu'aucune étude n'a démontré une diminution d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…11,12 Other studies have shown no change but none, to our knowledge, has shown a reduction in use after the legalization of recreational cannabis. 12 In Canada, only certain provinces allow the sale of cannabis by individuals. 16 Our study took place in the province of Québec, where the Société québécoise du cannabis (SQDC) has a monopoly on the sale of cannabis, which prevents the emergence of an open market.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…11,12 Other studies have shown no change but none, to our knowledge, has shown a reduction in use after the legalization of recreational cannabis. 12 In Canada, only certain provinces allow the sale of cannabis by individuals. 16 Our study took place in the province of Québec, where the Société québécoise du cannabis (SQDC) has a monopoly on the sale of cannabis, which prevents the emergence of an open market.…”
Section: Discussionmentioning
confidence: 82%
“…14 In the United States, a number of studies examining the impact of the legalization of recreational cannabis showed an increase in the use of cannabis after its legalization. 4,[11][12][13] These results should, however, be interpreted cautiously, given that it is difficult to separate the effect of the legislative change from emerging trends already present before the legalization. 11,12 Other studies have shown no change but none, to our knowledge, has shown a reduction in use after the legalization of recreational cannabis.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations